Sharing Economy as Unconventional Alternative to Traditional Transport Services - JURACKA, Denis; VALASKOVA, Katarina; JANOSKOVA, Katarina (Management Dynamics in the Knowledge Economy, 2023)
The sharing economy, as a developing business model, is becoming more and more popular. This phenomenon can be observed in many countries. The sharing economy, as a part of human life in its essence, has existed for a long time. In general, the sharing economy is considered an economic model where individuals or organizations share a certain type of property or, in this way, provide services for a financial reward. One of the most used sectors, where there is constant interest, is the shared transport of people, goods, and services. However, platforms operating in the shared transportation segment should be analysed from various points of view, such as their financial results and overall economic stability. The study is primarily focused on the sector of shared transport and transport services. The chief objective of the study was to demonstrate the impact of the COVID-19 pandemic on shared transport and transport services within the territory of the Slovak Republic. The analysis included ride-hailing platforms such as Bolt Services SK as well as food and dining delivery platforms such as Wolt Slovakia. Through appropriately chosen methods of financial and economic analysis, the situation of the platforms before and during the COVID-19 pandemic was determined. We also performed an analysis of the development of the number of cars and the related level of automobilization in the territory of the Slovak Republic, since the shared economy represents an alternative to conventional economic models.